Demographic shift in COVID-19 patients in Singapore from an aged, at-risk population to young migrant workers with reduced risk of severe disease. (February 2021) - Ngiam, Jinghao Nicholas; Chew, Nicholas; Tham, Sai Meng; Beh, Darius Lian-Lian; Lim, Zhen Yu; Li, Tony Y.W.; Cen, Shuyun; Tambyah, Paul Anantharajah; Santosa, Amelia; Sia, Ching-Hui; Cross, Gail Brenda
Highlights: There was a substantial shift in the population at risk of COVID-19 in Singapore over time. Successful control in the community protected an at-risk aging population. There were large outbreaks in the younger migrant worker population, with less severe disease. This resulted in one of the lowest case fatality rates globally. Abstract: Objectives: The vast majority of COVID-19 cases in Singapore have occurred amongst migrant workers. This paper examined trends in the hospitalised cases and tested the assumption that the low severity of disease was related to the relatively young affected population. Methods: All patients with PCR-positive SARS-CoV-2 admitted from February to April 2020 were divided into: (i) imported cases, (ii) locally-transmitted cases outside migrant worker dormitories and (iii) migrant worker dormitory cases. They were examined for underlying comorbidities, clinical progress and outcomes. Results: Imported cases ( n  = 29) peaked in mid-March 2020, followed by local cases ( n  = 100) in mid-April 2020; migrant worker cases ( n  = 425) continued to increase in late April 2020. Migrant worker cases were younger, had few medical comorbidities and less severe disease. As the migrant worker cases increased, the proportion of patients with pneumonia decreased, whilst patients presenting earlier in their illness and asymptomatic disease became more common. Conclusion: Singapore experienced a substantial shift in the population at risk of severe COVID-19. Successful control in the community protected an aging population. Large migrant worker dormitory outbreaks occurred, but the disease incurred was less severe, resulting in Singapore having one of the lowest case fatality rates in the world.